Ambiguity After the Constitutional Court Decision Number 90/PUU-XXI/2023 Regarding the Presidential Election - Indro Budiono; Adam Dinar Tanjung; Fathtor Rahman (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
The study investigates the ambiguity arising from the Constitutional Court's Decision No. 90/PUU-XXI/2023 concerning the presidential election in Indonesia. This decision, which pertains to Article 169 (q) of Law No. 7 of 2017 on General Elections, mandates a minimum age of 40 years for presidential and vice-presidential candidates. The research employs a qualitative design, analyzing legal texts and court decisions, and includes data from political parties and legal experts. The primary analytic strategy involves examining the implications of the Constitutional Court's decision on the political landscape and the legal framework governing elections. The findings indicate that the decision has led to significant confusion among political parties regarding the nomination of candidates who do not meet the minimum age requirement but have held public office. This ambiguity has highlighted the need for clearer legal provisions and interpretations to ensure fair and just elections. The study underscores the importance of the Constitutional Court's role in upholding substantive justice over formal legal requirements, emphasizing the principles of independence and impartiality. The main implications of this research suggest the necessity for consistent efforts to align legal products with fundamental political principles, ensuring a balance of power and prioritizing substantive justice. This is essential for establishing a good and democratic governance structure. The study also identifies the critical role of legal politics in shaping and implementing laws that reflect justice, common interests, and morality, advocating for systematic efforts to maintain the morality of politicians, state officials, and society as a whole.